PERAN GURU DALAM PENGELOLAAN KELAS - Abdullah Ali (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2021)
The purpose of this study was to determine the role of teachers in classroom management. The research method used in this research is descriptive analysis. The research approach used is qualitative. In collecting data using library research. The results showed that the teacher's role in classroom management was as a designer, organizer/manager, motivator in learning. And also implement school-based management